THE PROBLEM OF RECOGNIZING MINANGKABAU COMMON LAND OWNERSHIP RIGHTS BETWEEN THE MATRILINEAL SYSTEM AND INDONESIAN LEGISLATION: THE PROBLEM OF RECOGNIZING MINANGKABAU COMMON LAND OWNERSHIP RIGHTS BETWEEN THE MATRILINEAL SYSTEM AND INDONESIAN LEGISLATION - Chandra, Heru; Iriantoro, Agung; Teepapal, Tanawat (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
The communal land ownership system of the Minangkabau indigenous legal community based on the matrilineal system faces fundamental misalignment with Indonesia's national land law regulations. This research analyzes the characteristics of ulayat land ownership system based on Minangkabau customary law and its misalignment with UUPA. The research method employs a normative juridical approach with legislative analysis and literature study. The results show that Minangkabau ulayat land ownership system has unique characteristics in the form of hereditary communal ownership through maternal lineage with separation of rights and ownership concepts in the philosophy “hak bamiliek harato bapunyo, hak nan banampuharapo nan bamiliek”. The three-tiered hierarchical structure of nagari, tribal, and clan ulayat lands is managed based on the principle of “gangam bauntuak pagang bamasiang” which does not recognize the concept of buying and selling. Misalignment occurs because UUPA adopts an individual ownership paradigm that contradicts the Minangkabau communal system. Regulation through PP 18 of 2021 which enables the transformation of ulayat land into management rights actually creates a legal certainty paradox and potentially destroys the communal ownership system. The fragmentation of ulayat land to only 8.38% remaining intact reflects the failure of legal harmonization. A reconstruction of the national agrarian law paradigm is needed that can accommodate communal ownership characteristics without eliminating the essence of indigenous cultural values.